Troska o sprawy Kościoła w korespondencji ostatniej dekady życia Grzegorza z Nazjanzu - Widok, Norbert (Vox Patrum, 2016)
Analysis of approximately 165 letters of Gregory Nazianzen written by him in the last decade of his life revealed a large part of them devoted to his involvement in the current affairs of the ecclesial community. His departure from the position of the bishop of Constantinople, marked by a kind of failure, did not prompt him to react against the Church, but developed just an opposite attitude – increased mobilization of his strenght for the constant concern about the situation of the local Churches. This concern referred to the activities of the pastors of particular ecclesial communities, experiencing a variety of problems, deacons and presbyters, coming from his surroundings, as well as synods, which were to successfully resolve contentious issues. It should be remembered that Capadocian did not enjoy at that time good health. Despite suffering form various diseases, Gregory did not only focused on the treatment of poor health, but also continuesely appeared as an active member of the Church, especially that having still the bishops ordination, he could not completely withdraw from the pastoral obligations.